Pembatalan Perkawinan Berdasarkan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Tami Rusli (Law Faculty of Universitas Bandar Lampung, 2013)
To perform a marriage must meet the requirements defined religion as well as those determined by the law of marriage. If marriages already performed but do not meet the requirements that have been determined, it can be proposed cancellation.The problem in this study is how the legal consequences of annulment of marriage that has been decided by the Religious The research method used in this thesis is a normative approach legal research done by literature study with an assessment of secondary legal materials. Analysis of the data used is the juridical qualitative then the conclusion-is-deductively. From the results of this study concluded that annulment of a marriage that began after court ruling has binding legal force and effect from the time of the marriage, the decision annulment of marriage does not apply retroactively to children born of the marriage and community-property.